Assertive Speech Acts in Educational Discourses About Deep Learning on the Edukreatif.id Page - -, Meidila; Prayitno, Harun Joko (Jurnal Bahasa Indonesia Prima (BIP), 2026)
This study aims to describe the forms and pragmatic functions of assertive speech acts in digital educational discourse on Edukreatif.id during the 2023–2025 period. The research is motivated by the rapid development of digital educational media that not only disseminate information but also build credibility and legitimacy for educational ideas. Previous studies on assertive speech acts have mainly focused on classroom interactions, instructional videos, and social media, while web-based educational articles have received limited attention. This study employs a descriptive qualitative approach within the framework of pragmatics. The data consist of written utterances in Edukreatif.id articles containing assertive speech acts. Data were collected through documentation and note-taking techniques and analyzed using the extralingual pragmatic equivalent method through stages of reduction, categorization, interpretation, and conclusion drawing. Data validity was ensured through source and theoretical triangulation. The findings show that assertive speech acts on Edukreatif.id are dominated by the forms of stating, reporting, and affirming. These forms function to convey factual information, present educational activity reports, and emphasize the effectiveness of educational programs. The results indicate that assertive speech acts in digital educational discourse not only deliver information but also shape readers’ perspectives on educational issues.